Use of Neural Networks for Image Classification - Yakhyoyev Azizjon Azim ugli (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Neural networks have become the foundation of modern image classification systems, enabling significant advances in computer vision. Their ability to learn hierarchical representations directly from raw pixel data allows them to outperform traditional machine learning approaches. This article provides an overview of the principles, architectures, training techniques, and challenges associated with applying neural networks to image classification tasks. We analyze commonly used models, discuss optimization strategies, and highlight trends shaping the future of neural image classification.